Delimitation of call types of Red Crossbill (Loxia curvirostra) in the Western Palearctic. Issue 2 (3rd April 2019) - Martin, Ralph; Rochefort, Julien; Mundry, Roger; Segelbacher, Gernot
ABSTRACT: Vocal signals are important in many animal species for communication, coordination, and pair bonding and are especially well studied in birds. In the Red Crossbill ( Loxia curvirostra ) calls are an important trait for mate choice. In this species, calls having the same function (e.g., flight calls or excitement calls) are known to be clustered in distinct groups, so called 'call types'. Each individual utters only calls of one call type. The driving force for the differentiation of Red Crossbill call types in the Palearctic remains unknown, as call types often overlap in space, and time and birds can be seen feeding on the same seeds. In this study, we investigated calls of crossbills, recorded within seven years in the Western Palearctic. We found at least 17 distinct call types of Red Crossbill and at least two call types of Parrot Crossbill ( Loxia pytyopsittacus ). There were obvious differences in call type delimitation between the northern and southern part of the study area. We argue this is in conflict with the ecological differentiation hypothesis and propose that there are other or further driving forces for this differentiation process.